Individual alpha-frequency correlates with amplitude of visual evoked potential and hemodynamic response - Koch, Stefan P.; Koendgen, Sophie; Bourayou, Riad; Steinbrink, Jens; Obrig, Hellmuth (NeuroImage (Orlando, Fla.), 2008)
In a simultaneous electroencephalography (EEG) and near-infrared spectroscopy (NIRS) study, the predictive value of the individual alpha-frequency at rest (IAF) for the amplitude of neuronal and vascular responses to visual stimulation was investigated. Across subjects, we find (i) an inverse relationship between IAF and the amplitude of the alpha-rhythm at rest. The IAF also predicts (ii) the amplitude of the visual evoked potential (VEP), as well as (iii) the amplitude of the alpha-rhythm during stimulation. Most importantly, (iv) IAF correlates with the oxygenation response to visual stimulation: A high IAF predicts a low alpha-amplitude at rest, a small VEP amplitude and a small oxygenation response. Conversely, a low IAF predicts high alpha-amplitude and larger electrophysiological and vascular responses to stimulation. Based on these findings, we assume that the relationship between IAF and neuronal and vascular response stems from the size of the network recruited for visual processing. The relation between IAF, alpha-amplitude, evoked potential and vascular response is discussed in the framework of a simple heuristic model. The results may partly explain the large intersubject variability observed in recently published concurrent EEG-fMRI studies.